Diphtheria Outbreak in Serang City, Banten, Indonesia, 2024: Epidemiological Investigation and Response - Rini Fatihatun Nisa; Nenden Hikmah Laila; Nurhayati Adnan (Jurnal teknologi Kesehatan Borneo, 2024)
Diphtheria is an infectious disease and often causes outbreak. Despite a significant global decrease in diphtheria cases due to effective vaccines, there's still a risk transmission for individuals who unvaccinated or incompletely vaccinated. A positive culture for Corynebacterium diphtheriae was reported in a diphtheria suspect in Serang City and an outbreak investigation was carried out. This study aimed to investigate the outbreak, identify risk factors, and recommend control measures. Data were collected through interviews and field observations to close contacts consist of household contacts, neighbors and school and we reviewed immunization coverage from the Public Health Center. Based on the investigation, it was shown that a 6 years-old male with signs and symptoms of Fever, Sore Throat, Swollen Neck, Pseudomembrane, difficulty swallowing, mouth ulcers, cough and vomiting, and positive results for toxigenic corynebacterium diphtheriae var intermedius. Risk factors for transmission are low immunization coverage, high population density, and mobilization. No additional cases were identified, but some close contacts were at risk of transmission due to unvaccinated. We recommend implementing Outbreak Response Immunization (ORI) as a critical measure to interrupt transmission.